Non-phase matched spontaneous parametric down conversion in ultra-thin lithium niobate - Okoth, Cameron; Santiago, Tomás; Cavanna, Andrea; Chekhova, Maria (Optics InfoBase Conference Papers, 2019)
We report the generation of entangled photon pairs via type-0 spontaneous parametric down conversion in ultra-thin lithium niobate in which momentum between the.
CRIS-Team Scopus Importer:2019-07-09